Delay in Decision-Making Affecting Construction Projects: A Sustainable Decision-Making Model for Mega Projects - Shabir Hussain Khahro, Shabir Hussain Khahro; Haseeb Haleem Shaikh, Haseeb Haleem Shaikh; Noor Yasmin Zainun, Noor Yasmin Zainun; Basel Sultan, Basel Sultan; Qasim Hussain Khahro, Qasim Hussain Khahro (Mdpi, 2023)
The construction industry is one of the world’s fastest-growing industries, since it directly and indirectly contributes to several other industries. It has been observed that delays in the decision making of important stakeholders negatively impact construction projects. Thus, this has multiple consequences on project performance. Consequently, the purpose of this study was to identify the primary causes of delayed decision-making and offer a decision support model for timely construction project decisions. For factor identification, a comprehensive literature analysis was conducted, followed by an analysis of questionnaire responses of ninety-one professionals. For data analysis, the relative importance index (RII) method was applied. The results indicate that client decision-making delays pose a substantial obstacle for building projects. The early decision-making process is impacted by a lack of technical competence, incomplete paperwork, poor leadership, and coordination/communication issues. The proposed model could also assist project practitioners in improving their project decision making. This research study encourages stakeholders to create and implement an efficient decision-making procedure for timely project decisions. A procedure for decision making that is successful could decrease delays in the decision-making process and prevent conflicts and disputes in projects.